Molecular tissue markers integrated: A mathematical model approach to evaluating and predicting prostate cancer using molecular tissue markers: Integrirani molekularni tkivni označevalci: matematični model v pristopu k oceni in predvidevanju raka prostate s tkivnimi molekularnimi označevalci - Munda, Mihael (Acta Medico-Biotechnica, 2024)
Purpose: The standard criteria available for the diagnosis of prostate cancer often do not sufficiently predict the course or outcome of this common disease. Evaluating molecular tissue markers, especially those that mark apoptosis and proliferation, in an integrated mathematical model, could contribute to a better understanding of the development and pathogenesis of this disease, aid in the selection of adequate therapies, and open new avenues of therapeutic research.Materials and methods: Paraffin-embedded prostatectomy specimens were stained according to an immunohistochemical protocol for p53, bcl-2, and CD105. A mathematical model was developed, which incorporated values of tissue markers according to their apoptotic/proliferative characteristics.Results: The results of tissue marker expression and mathematical modeling were correlated with patient clinical data. We showed that tissue marker values correlated better with clinical data when tissue markers values were incorporated in a mathematical model than when applied alone.
Keywords: mathematical model, prostate cancer, tissue marker, p53, bcl-2, CD105